2012
DOI: 10.1095/biolreprod.111.093658
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Shock-Domain Protein A (CSDA) Contributes Posttranscriptionally to Gonadotropin-Releasing Hormone-Regulated Expression of Egr1 and Indirectly to Lhb1

Abstract: Gonadotropin-releasing hormone (GnRH), a hypothalamic neurohormone, regulates transcription of Lhb in gonadotrophs indirectly through transient induction and accumulation of EGR1, a zinc finger transcription factor. AlphaT3 and LbetaT2 cell lines model gonadotrophs at two distinct stages of development, prenatal and postnatal expression of Lhb. Although GnRH induces EGR1 in both cell lines, the levels of the DNA-binding protein are lower and disappear more quickly in alphaT3 than in LbetaT2 cells. Herein we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
3
0
1
Order By: Relevance
“…The general function of CSD proteins are as participants in mRNA stability and as mRNA chaperones that promote translation. In LβT2 cells CSDA is highly expressed relative to αT3-1 cells and binds to the 3’ UTR of Egr1 mRNA (Chauvin et al, 2012). Differences in CSDA expression correlate to differences in expression of EGR1.…”
Section: Post-transcriptional Control Of Gene Expressionmentioning
confidence: 99%
“…The general function of CSD proteins are as participants in mRNA stability and as mRNA chaperones that promote translation. In LβT2 cells CSDA is highly expressed relative to αT3-1 cells and binds to the 3’ UTR of Egr1 mRNA (Chauvin et al, 2012). Differences in CSDA expression correlate to differences in expression of EGR1.…”
Section: Post-transcriptional Control Of Gene Expressionmentioning
confidence: 99%
“…A total of 24 genes were selected with degrees >72; EGR1, MAPK1, MYC, Bcl2 and calmodulin 1 (CALM1). EGR1, a primary response gene that encodes a zinc finger DNA-binding protein, is reported to be critical in cancer metastasis and tumor invasion (31). This gene was found to be regulated by gonadotropin-releasing hormone (GnRH) to regulate the expression of luteinizing hormone β polypeptide, one of the GnRH-responsive genes, and was revealed to be associated with prolactinoma in a previous study (31).…”
Section: Discussionmentioning
confidence: 99%
“…EGR1, a primary response gene that encodes a zinc finger DNA-binding protein, is reported to be critical in cancer metastasis and tumor invasion (31). This gene was found to be regulated by gonadotropin-releasing hormone (GnRH) to regulate the expression of luteinizing hormone β polypeptide, one of the GnRH-responsive genes, and was revealed to be associated with prolactinoma in a previous study (31). Previous studies have suggested that genipin inhibits the proliferation of various cancer cells by promoting EGR1 function, such as gastric, colon and breast cancer (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Συγκεκριμένα, δείχθηκε σε καλλιέργειες κυττάρων LβT2 δείχθηκε ότι η Ρ 4 μπορεί να καταστείλει την έκφραση LHB mRNA μετά την πρόσδεσή της στον πυρηνικό υποδοχέα. Έλλειψη έκφρασης του LHB προκαλεί υπογονιμότητα (61).…”
Section: Lhbunclassified